Investigation of food meat value obtained from bull-calves of Polissya meat breed with different types of higher nervous activity - Паска, Марія Зіновіївна (Technology audit and production reserves, 2015)
Meat productivity of cattle is formed by wide range of morphological, biological, physiological characteristics, which depend on the species, genotype of animals, environmental conditions, type of higher nervous activity, diet and usefulness is measured by such indicators as the cost of feed per unit increase; body weight, absolute and relative growth rates, carcass yield, meat quality. Therefore, the study of biochemical processes in fattening bull-calves of Polissya meat breed, depending on the type of higher nervous activity and the effect of feeding feed additive "Mikrolipovit" on the main indicators of metabolism and meat productivity is extremely important. The increase in the above parameters and urea indicates the enhancement of protein metabolism in calves, glucose, carbohydrate metabolism and total lipids resulting in increased meat productivity, improved slaughter performance and meat quality characteristics. Based on the data content and the ratio of essential nutrients, biological value of meat its technological properties must be concluded that the meat of calves of different types of higher nervous activity, characterized by optimum chemical composition and high usefulness protein that is fully consistent needs of consumers. Maximizing productivity of fattening bull-calves, compared to other research groups, found in animals such as inert strong equilibrium type of higher nervous activity (3rd group).